VD_FINDINFO Arrêt / 2010 / 1330 vom 17. September 2010 - VD Tribunal cantonal (2010)
TRAITEMENT HOSPITALIER, LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE, MALADIE DES ORGANES GÉNITO-URINAIRES | 32 LAMal, 33 al. 1 LAMal, 33 al. 3 LAMal, 41 al. 2 LAMal, 41 al. 2 let. b LAMal, 41 al. 3 LAMal, 33 let. a OAMal, 33 let. c OAMal, 1 OPAS